2021
DOI: 10.1080/13547860.2020.1868107
|View full text |Cite
|
Sign up to set email alerts
|

Regional income disparities and convergence clubs in Indonesia: new district-level evidence

Abstract: This paper aims to re-examine the regional convergence hypothesis on income in Indonesia over the 2000-2017 period. By applying a non-linear dynamic factor model, this paper tests the club convergence hypothesis using a novel dataset of income at the district level.The results show significant five convergence clubs in Indonesian districts' income dynamics, implying the persistence of income disparity problems across districts even after implementing the decentralization policy. The subsequent analysis reveals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…Closing gaps in education is vital to improving equality of opportunities (Tomul, 2009). Our results support Aginta et al (2021), who found some convergence in income within districts and within provinces in Indonesia, although noting persistency in income inequality across regions. Inequality primarily results from imbalances in economic and development issues that remain unresolved in Indonesia (Siburian, 2020).…”
Section: Figure 1: Two-lines Testsupporting
confidence: 80%
“…Closing gaps in education is vital to improving equality of opportunities (Tomul, 2009). Our results support Aginta et al (2021), who found some convergence in income within districts and within provinces in Indonesia, although noting persistency in income inequality across regions. Inequality primarily results from imbalances in economic and development issues that remain unresolved in Indonesia (Siburian, 2020).…”
Section: Figure 1: Two-lines Testsupporting
confidence: 80%
“…These results highlight the importance of capital accumulation and efficiency improvements in the promotion of growth productivity as well as reducing the disparities among regions in Indonesia. Using a district-level dataset, Aginta et al (2021) evaluate the prospects of regional income convergence in the postdecentralization era. Their results indicate five clubs of convergence for 514 districts with the richest group dominated by big cities and regions with natural resources.…”
Section: Observation (Sample)mentioning
confidence: 99%
“…Their results suggests two convergence clubs for each socioeconomic indicator. Using a novel district-level data set, Aginta, Gunawan, and Mendez (2020) apply the club convergence framework of Phillips and Sul (2007) to evaluate regional income convergence in Indonesia. They find five convergence clubs across 514 districts over the 2000-2017 period.…”
Section: Testing For Economic Convergence Across Indonesian Regionsmentioning
confidence: 99%
“…Most studies about Indonesia, however, have focused on only a narrow set of variables. Sakamoto (2007) and Aginta et al (2020), for instance, only focus on income, while Mendez (2020) only focuses on efficiency. To the best of our knowledge, only Kurniawan et al (2019) evaluate the dynamics of regional convergence across multiple indicators: per-capita GDP, Gini index, enrollment rate, and fertility rate.…”
Section: Testing For Economic Convergence Across Indonesian Regionsmentioning
confidence: 99%
See 1 more Smart Citation